2020
DOI: 10.1007/s11557-020-01584-6
|View full text |Cite
|
Sign up to set email alerts
|

The bright and shaded side of duneland life: the photosynthetic response of lichens to seasonal changes is species-specific

Abstract: Terricolous lichens are relevant associates of biological soil crusts in arid and semiarid environments. Dunes are ecosystems of high conservation interest, because of their unique, vulnerable and threatened features. The function of lichens is affected by the changing seasons and different microhabitat conditions. At the same time, inland dunes are less investigated areas from the terricolous lichens point of view. We explored the effect of seasonal variation and different micro-environmental conditions (aspe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
29
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 16 publications
(33 citation statements)
references
References 54 publications
4
29
0
Order By: Relevance
“…Our results showed that the site had higher explanatory power than dune side. Since we could not find any significant difference in the climate between the two study site (Veres et al 2020) history could also play an important role in developing different lichen communities.…”
Section: Species Pools Of the Two Study Sitesmentioning
confidence: 60%
See 1 more Smart Citation
“…Our results showed that the site had higher explanatory power than dune side. Since we could not find any significant difference in the climate between the two study site (Veres et al 2020) history could also play an important role in developing different lichen communities.…”
Section: Species Pools Of the Two Study Sitesmentioning
confidence: 60%
“…The list of terricolous lichen species at the Bugacpusztaháza (BU) and Fülöpháza (FH) sites according to previous authors and collectors (Gallé 1973;Lőkös & Verseghy 2001) Sampling was carried out in late autumn and during wintertime because it was more advantageous to estimate the cover of the different lichen growth forms than in summer when they are usually in a dry condition. Our previous long-term study (Veres et al 2020) revealed a significant difference in microclimate between the north-east (NE) and south-west (SW) facing dune sides or aspect of the sites. The more exposed, SW-facing slopes are considered arid; the NE-facing sides are considered less arid (hereafter 'humid') dune sides.…”
Section: Sampling Methodsmentioning
confidence: 93%
“…Consequently, the net effect of competition and facilitation is the co‐occurrence of lichen symbiosis and vascular plants. Competitive effects are important for structuring lichen communities at a global scale, as lichen symbiosis may confer a competitive advantage and promote stability (Rogers, 1971; Bowker et al ., 2016; van Zuijlen et al ., 2020; Veres et al ., 2020). However, drought conditions may favour lichen development over vascular plants in drylands and give greater tolerance by lichens to extreme dryness, light and temperature (Belnap, 2006; Ding & Eldridge, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…For example, pH is important in predicting the relative abundance of Verrucaria and Endocarpon , but not Rinodina . We found that precipitation seasonality is a potential predictor of Rinodina , suggesting that it is sensitive to changes in seasonal precipitation, similar to lichenised fungi in general (Bowker et al ., 2016; Veres et al ., 2020). While fluctuations in seasonal precipitation might favour some lichenised taxa (Lange, 1953; Rogers, 1971), high levels of hydration, particularly at high temperatures, are known to reduce photosynthetic levels of lichen symbiosis despite their high respiration (Rogers, 1971).…”
Section: Discussionmentioning
confidence: 99%
“…Finally, we hypothesized that species belonging to more tolerant functional groups would show a higher capacity to recover after the stress exposure than sensitive species. To test our hypotheses, we used chlorophyll a fluorescence as a sensitive but non-destructive method for assessing the response of photosynthetic organisms to environmental changes [ 33 ]. Understanding the response of these sensitive elements of ecosystems to multiple environmental stressors is a primary goal to improve the use of lichens as indicators for environmental protection and predict the potential consequences of global change on ecosystem functioning.…”
Section: Introductionmentioning
confidence: 99%